Impact of the COVID-19 Pandemic on the Management of Staphylococcus aureus Bloodstream Infections in a Tertiary Care Hospital - Christian W. Böing; Neele J. Froböse; Frieder Schaumburg; Stefanie Kampmeier (Pathogens, 2023)
Staphylococcus aureus bacteremia (SAB) is associated with a high mortality rate. The clinical outcome of SAB patients highly depends on early diagnosis, adequate antibiotic therapy and source control. In the context of the COVID-19 pandemic, the health care system faced additional organizational challenges and the question arose whether structured screening and triaging for COVID-19 and shifting resources influence the management of SAB. Patients (n = 115) with SAB were enrolled in a retrospective comparative study with historical controls (March 2019–February 2021). The quality of SAB therapy was assessed with a point score, which included correct choice of antibiotic, adequate dosage of antibiotic, sufficient duration of therapy, early start of therapy after receipt of findings, focus search and taking control blood cultures 3–4 days after starting adequate antibiotic therapy. The quality of treatment before and after the onset of the COVID-19 pandemic were compared. No significant differences in the total score points were found between the pre-COVID-19 and COVID-19 cohort. All quality indicators, except the correct duration of antibiotic therapy, showed no significant differences in both cohorts. Furthermore, there were no significant differences in the outcome between both cohorts. The treatment quality of SAB therapy was comparable before and during the COVID-19 pandemic.